Analisis Gaya Bahasa Cerpen dalam Portal Berita Online Jawa Pos Edisi Februari 2023 - Anjani, Sela; Sugiarti, Dewi Herlina; Suprihatin, Dewi (Peneliti.net, 2024)
This research aims to describe, (1) the use of language styles in the weekly Jawa Pos short stories, and (2) the language styles that tend to or appear most frequently in the weekly Jawa Pos short stories. To achieve this goal, researchers used a qualitative descriptive research design. The subject of this research is short stories in the February 2023 edition of the weekly Jawa Pos newspaper. The object of the research is the use of language style in the short stories of the weekly Jawa Pos newspaper. The method used to collect data is the documentation method. The results of this research show that: (1) the language styles in the Jawa Pos weekly short stories are very diverse. There are 20 types of language styles, namely imagery, metaphor, personification, antithesis, pleonasm, anticipation, correction, hyperbole, climax, paradox, euphemism, antonomasia, metonomia, paralism, anaphora, mesodilopsis, epanalepsis, epizeuksis, assonnsi, and tautotes. (2) the language style that is dominant or often appears in the short stories of the Jawa Pos Online News Portal, namely, the hyperbole language style totaling 16 data.